Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1108/vjikms-07-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the moderating effect of humble leadership behaviour on motivational factors and knowledge-sharing intentions: evidence from Jordanian public organisations

Abstract: Purpose The purpose of this paper is to empirically investigate the moderating effect of humble leadership on the relationship between different intrinsic and extrinsic motivational factors and employee’s knowledge-sharing intention. Design/methodology/approach Responses of 236 employees in public organisations in the country of Jordan were collected via the completion of an online survey. The study data was analysed using structural equation modelling. Findings This study found that humble leadership supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 89 publications
6
15
1
1
Order By: Relevance
“…The results indicated the reciprocity can significantly improve the online KS among the employee, this result in line with previous studies [4,16,30]. Reciprocity benefits can heavily influence individual attitudes toward online KS.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The results indicated the reciprocity can significantly improve the online KS among the employee, this result in line with previous studies [4,16,30]. Reciprocity benefits can heavily influence individual attitudes toward online KS.…”
Section: Discussionsupporting
confidence: 90%
“…Enjoyment statistically has a significant impact on the intention of KS [25]. In addition, Al Hawamdeh and AL-edenat [4] reported that enjoyment could enhance the KS and enjoyment has a significant impact on KS.…”
Section: Enjoymentmentioning
confidence: 89%
See 3 more Smart Citations